COMPARISON OF FUNCTIONAL OUTCOME BETWEEN NEUTRAL WITH RESIDUAL MILD CORONAL ALIGNMENT POST PRIMARY TOTAL KNEE ARTHROPLASTY: THREE YEARS FOLLOW-UP IN MAKASSAR, SOUTH SULAWESI - Mario, Ardian, Sakti, Muhammad, Usman, M. A., Rahmansyah, Nur (South Eastern European Journal of Public Health, 2025)
Introduction: Total Knee Arthroplasty (TKA) is an orthopedic procedure that replaces a damaged knee joint with an artificial prosthesis to reduce pain and restore knee function. Neutral coronal alignment post-TKA is often considered a standard of success, although some studies suggest that mild residual coronal alignment might provide better clinical outcomes. This study aims to compare the clinical functional outcomes between neutral coronal alignment and mild residual coronal alignment in patients post-TKA after a three-year follow-up in Makassar, South Sulawesi. Method: This research is a prospective observational study conducted at RSUP Wahidin Sudirohusodo, Makassar, involving patients with grade III or IV knee osteoarthritis who underwent TKA from January to December 2020. Samples were taken through consecutive sampling and included patients over 40 years old with either neutral coronal alignment or mild residual coronal alignment post-surgery. Clinical functional outcomes were measured using The Knee Society Score: Short Form and The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score list. Results: This study utilized the Short Form Knee Society Score (SF-KSS) to evaluate total knee arthroplasty, along with The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score list, where a p-value > 0.05 was found, indicating no significant difference. Conclusion: There were no notable differences in clinical functional outcomes between the neutral and mild residual mechanical alignment groups. This can serve as a reference in performing total knee arthroplasty, allowing surgeons to preserve more tissue structures and bone to achieve mild residual alignment rather than performing aggressive releases to achieve neutral alignment.